2016
DOI: 10.1111/nph.13937
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and diversification in the African ‘sky islands’: insights from fossil‐calibrated molecular dating of Lychnis (Caryophyllaceae)

Abstract: SummaryThe flora on the isolated high African mountains or 'sky islands' is remarkable for its peculiar adaptations, local endemism and striking biogeographical connections to remote parts of the world. Ages of the plant lineages and the timing of their radiations have frequently been debated but remain contentious as there are few estimates based on explicit models and fossil-calibrated molecular clocks.We used the plastid region maturaseK (matK) and a Caryophylloflora paleogenica fossil to infer the age of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 71 publications
1
43
0
1
Order By: Relevance
“…Hence, in such a tree line ascent scenario, the total area, and thus also population sizes of alpine and heathland Table S5) species, would shrink, potentially leading to local species extinction as tree lines advance toward isolated mountain tops (cf. Dirnb€ ock, Essl, & Rabitsch, 2011;Gizaw et al, 2016). Studies in the Alps have shown that it is the abandonment of traditional pasture management, rather than increasing temperatures, that is driving the observed tree line ascent there (Braunisch et al, 2016;Carlson, Renaud, Biron, & Choler, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in such a tree line ascent scenario, the total area, and thus also population sizes of alpine and heathland Table S5) species, would shrink, potentially leading to local species extinction as tree lines advance toward isolated mountain tops (cf. Dirnb€ ock, Essl, & Rabitsch, 2011;Gizaw et al, 2016). Studies in the Alps have shown that it is the abandonment of traditional pasture management, rather than increasing temperatures, that is driving the observed tree line ascent there (Braunisch et al, 2016;Carlson, Renaud, Biron, & Choler, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, origins of some species endemic to sky islands can be attributed to environmental and climatic changes (Robin et al, ). In addition, most available studies, based on sequence variations of cytoplasmic DNA and/or internal transcribed spacers, suggested that the radiative diversifications of these sky island species were dated to have occurred during the Pleistocene (Cox et al, ; Salerno et al, ; Gizaw et al, ; Diazgranados & Barber, ) or earlier when the local mountains arose or experienced radical geological oscillations (He & Jiang, ; Mastretta‐Yanes et al, ). However, none of these previous studies used statistical tests to examine how the sky island species diverged or originated, based on genomic data from next‐generation sequencing and the recently developed coalescent approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The afro-montane forest vegetation alone is more species rich than the ericaceous and afro-alpine vegetation taken together (Hedberg, 1957;Smith & Cleef, 1988;Fjeldså & Lovett, 1997;Gehrke & Linder, 2014). However, except for some mostly afro-alpine plant lineages such as giant senecios (Knox & Palmer, 1995) and giant lobelias (Knox & Palmer, 1998) that became popular examples of sky island radiations, and for some genera showing conspicuously disjunct distributions (e.g., Lychnis L. [Caryophyllaceae]: Popp & al., 2008;Ranunculus L. [Ranunculaceae], Carex L. [Cyperaceae] and Alchemilla L. [Rosaceae]: Gehrke & Linder, 2009;Gehrke & al., 2015), the mountainous floras of tropical Africa remain little studied from a biogeographic and phylogeographical point of view (but see Kebede & al., 2007;Dimitrov & al., 2012;Gizaw & al., 2016a).…”
Section: Introductionmentioning
confidence: 99%